KEMAMPUAN MENULIS BIOGRAFI MELALUI MEDIA PEMBELAJARAN VIDEO DOKUMENTER SISWA KELAS VIII SMP TAHUN AJARAN 2017/2018 - Nadia, Lia; Marshanda, Dea; Suhaniah, Acih; Hilaliyah, Tatu; Tanjung, Elma Fiana (Universitas Batanghari, 2024)
This research aims to describe the influence of documentary video media on the writing abilities of eighth-grade students at SMP Al-Hikmah Medan during the academic year 2017-2018. The research was conducted at SMP Al-Hikmah Medan with a population of 59 students from two classes, all of whom were included in the research sample. Class VIII 2 was designated as the experimental group, while Class VIII 1 served as the control group. This research utilized an experimental method, a technique designed to reveal clear facts about the phenomena under investigation. The data collection tool employed was a written test. The writing abilities of biographies using documentary video media in the experimental class were deemed good, as 13 students (43.33%) fell within the 80-100 range, 13 students (43.33%) achieved a